2019
DOI: 10.1021/acs.analchem.9b03225
|View full text |Cite
|
Sign up to set email alerts
|

Breaching the 10 Second Barrier of Total Analysis Time for Complex Matrices via Automated Coated Blade Spray

Abstract: In the development of modern analytical workflows, parameters such as sample turnaround time, cost of analysis, and ease of use must be prioritized. Automation enables reductions in total analysis time, human intervention, and cost per sample. In this report, a suitable automated coated blade spray (CBS) workflow is proposed for the screening and quantitation of multiple substances (i.e., drugs of abuse and pesticides) in complex matrices. In an attempt to reduce the total sample analysis time, several paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…For instance, Kasperkiewicz et al proposed for the first time optimization of extraction time based on signal‐to‐noise ratios instead of mere instrumental signal. The work demonstrated that it is important to consider the coextraction of other sample components as this may affect quantitative results 28 . In addition, the same work demonstrated that, because of the power of state‐of‐art instrumentation, spray times can be shortened and instrumental analysis time driven by the total number of analytes that can be monitored.…”
Section: Cbs‐msmentioning
confidence: 98%
See 4 more Smart Citations
“…For instance, Kasperkiewicz et al proposed for the first time optimization of extraction time based on signal‐to‐noise ratios instead of mere instrumental signal. The work demonstrated that it is important to consider the coextraction of other sample components as this may affect quantitative results 28 . In addition, the same work demonstrated that, because of the power of state‐of‐art instrumentation, spray times can be shortened and instrumental analysis time driven by the total number of analytes that can be monitored.…”
Section: Cbs‐msmentioning
confidence: 98%
“…Since its inception, the use of CBS has been primarily focused on bioanalysis 31 . Recently, the technology was shown to be also suitable for rapid food screening and quantitation by work that has set important breakthroughs, not only in food analysis but also in microextraction technology interfaces with MS instrumentation 28,29 . For instance, Kasperkiewicz et al proposed for the first time optimization of extraction time based on signal‐to‐noise ratios instead of mere instrumental signal.…”
Section: Cbs‐msmentioning
confidence: 99%
See 3 more Smart Citations